2012
DOI: 10.1007/s00394-012-0374-9
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxyisoleucine stimulates glucose uptake by increasing surface GLUT4 level in skeletal muscle cells via phosphatidylinositol-3-kinase-dependent pathway

Abstract: Results suggest that 4-HIL stimulates glucose uptake in L6-GLUT4myc myotubes by enhancing translocation of GLUT4 to the cell surface in a PI-3-kinase/AKT-dependent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Increased glucose uptake, increased Akt phosphorylation on Ser 473 (pAkt), increased PI3K, increased glucose transporter 4 (GLUT4) [103] Insulin-resistant skeletal muscle (L6 myocytes)…”
Section: Experimental Results Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Increased glucose uptake, increased Akt phosphorylation on Ser 473 (pAkt), increased PI3K, increased glucose transporter 4 (GLUT4) [103] Insulin-resistant skeletal muscle (L6 myocytes)…”
Section: Experimental Results Referencementioning
confidence: 99%
“…In rat muscle cells, it has been observed that glucose uptake and GLUT-4 translocation to the plasma membrane were increased after 16 h exposure to 4-OHIle [103]. The basal phosphorylation of Akt (Ser-473) increased after treatment with 4-OHIle, but mRNA expression of total Akt, IRS-1, GLUT-4, and glycogen synthase kinase-3β (GSK-3β) was unchanged.…”
Section: Experimental Results Referencementioning
confidence: 99%
“…Mulberry leaf has been reported to increase glucose uptake in primary adipocytes [52], DNJ increased glucose uptake in 3 T3-L1 adipocytes [53] and 4-OH-IIe from fenugreek seed increased glucose uptake in L6-GLUT4myc myotubes [54]. Ginsenoside Rb1 from American ginseng was also shown to stimulate basal and insulin-mediated glucose uptake in 3 T3-L1 adipocytes and C2C12 myotubes [55].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in adipose tissue expression of PDK1 and GLUT4 in our study was significantly blunted by the botanical test formula. While fenugreek seed, mulberry leaf and American ginseng individually have been shown to increase the expression of GLUT4 in 3 T3-L1 adipocytes and in insulin resistant animal models [5254, 63, 64], a PDK1/GLUT4-mediated mechanism has not been previously described for a formula containing these herbal extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 4-HIL was proven to possess glucosedependent insulinotropic and insulin-sensitizing effects in an in vivo rodent model (Broca et al 2000(Broca et al , 2004. Furthermore, 4-HIL was demonstrated to stimulate glucose uptake by increasing the surface GLUT4 level in skeletal muscle cells and attenuate FFA-induced insulin resistance through inhibiting ROS-mediated inflammation and facilitating IRS-1/AKT/ AS160 signaling pathway in skeletal muscle cells (Jaiswal et al 2012;Maurya et al 2014). Insulin response mediated by 4-HIL is strictly dependent on the glucose concentration.…”
mentioning
confidence: 96%